I found a family through sociotherapy - Nyiramana, Mameritha (Torture Journal, 2018)
I was born in the Southern Province of Rwanda. My parents were cattle keepers. We were ten children. We are now four because the other six died during the genocide. Before the genocide, I never experienced any violence. The first time I encountered violence was during the genocide, when I was nineteen years old. I was raped and I gave birth to a child of the Interahamwe. I have good memories of my life before the genocide, especially of meeting up with my friends. It hurts that I no longer see them, because the genocide separated us. I now live with my three children and a husband. The oldest child is seventeen years old, the second one is three years old, and the last one is one year old.